G516(P) Palliative care services for children and young people: Realist review of the literature. (27th April 2016) - Mitchell, S; Bennett, K; Morris, A; Dale, J
Abstract : Background: Caring for the growing population of children and young people (CYP) living with life-limiting conditions and life threatening conditions represents a significant challenge for the UK healthcare system. The delivery of palliative care services for CYP in the UK is inconsistent, despite the development of guidance, recommendations and service standards. This realist review assesses the current evidence for palliative care service delivery for CYP and their families and how it relates to current practice and policy. Aims: To investigate the current evidence for palliative care service delivery for CYP and their families and to develop implementable theories in order to address the gap between policy recommendations and clinical practice by addressing the research questions: What is the current evidence for palliative care service delivery for CYP and their families? How does this relate to current practice and policy? Review methods: Realist review was conducted as it allows the review question to be expanded to considered "what is it about this intervention that works, for whom and in what circumstances?" and takes into account the complexity of the intervention. The goal is to examine and understand how context influences mechanisms to generate outcomes: context-mechanism-outcomes (CMO) configurations. Through a process of CMO abstraction, theories can be created. Results: 20 articles were identified for inclusion. Four major themes were identified: CYP: CYP wish to be involved in decisions about their care when possible; Families: care for the family is necessary. Families value both practical and emotional support for siblings and wish for support that continues into bereavement; Healthcare professionals: continuity of care allows families to have open and honest conversations with healthcare professionals who they know Healthcare system: families value not having to retell their story on numerous occasions. There is opportunity for more effective integration and effective communication between professionals. Conclusions: The review provides an in-depth insight into how and why services are seen as effective by CYP and their families. The major themes identified correspond with those highlighted in UK policy and guidelines. This review proposes theories which should aid the future transition of policy into practice.